Regulation of glucose-stimulated insulin secretion by ATPase Inhibitory Factor 1 (IF1) - Kahancová, Anežka; Sklenář, Filip; Ježek, Petr; Dlasková, Andrea (FEBS letters, 2018)
ATPase Inhibitory factor 1 (IF1) is an endogenous regulator of mitochondrial ATP synthase, which is involved in cellular metabolism. Although great progress has been made, biological roles of IF1 and molecular mechanisms of its action are still to be elucidated. Here, we show that IF1 is present in pancreatic β-cells, bound to the ATP synthase also under normal physiological conditions. IF1 silencing in model pancreatic β-cells (INS-1E) increases insulin secretion over a range of glucose concentrations. The left-shifted dose-response curve reveals excessive insulin secretion even under low glucose, corresponding to fasting conditions. A parallel increase in cellular respiration and ATP levels is observed. To conclude, our results indicate that IF1 is a negative regulator of insulin secretion involved in pancreatic β-cell glucose sensing.
Keywords: Animals; INS-1E cells; Rats, Wistar; Cell Line, Tumor; IF1; nádorové buněčné linie; Oxygen Consumption; beta-buňky; ATPase Inhibitory Protein; Insulin; diabetes; Proteins; protein inhibující ATPasu; proteiny; glukosa; Glucose; Insulin-Secreting Cells; ATP synthase; β-cells; krysa rodu Rattus; insulin secretion; zvířata; inzulin; Rats; spotřeba kyslíku; potkani Wistar